Setting priorities for health education research: A mixed methods study. (2nd September 2019) - Palermo, Claire; King, Olivia; Brock, Tina; Brown, Ted; Crampton, Paul; Hall, Helen; Macaulay, Janet; Morphet, Julia; Mundy, Matthew; Oliaro, Louise; Paynter, Sophie; Williams, Brett; et al.
Abstract: Introduction: Identifying priority research topics that meet the needs of multiple stakeholders should maximize research investment. Aim: To identify priorities for health education research. Methods: A three-stage sequential mixed methods study was conducted. Priorities for health education research were identified through a qualitative survey with 104 students, patients, academics, and clinicians across five health sciences and 12 professions (stage 1). These findings were analyzed using framework analysis and transposed into a quantitative survey whereby 780 stakeholders rated and ranked the identified priorities. Descriptive statistics identified priorities, exploratory factor analysis grouped priorities and differences between stakeholders were determined using Mann–Whitney U tests (stage 2). Six individual or group interviews with 16 participants (stage 3) further explicated the results from previous stages. Results: Of 30 priorities identified, the top were: how best to ensure students develop the required skills for work; how to promote resiliency and well-being in students; and ensuring the curriculum prepares students for work. For the majority of priorities, no significant differences were found between different stakeholder groups. Conclusions: These findings will be used to inform health educational research strategy both locally and nationally. Further research should explore if setting priorities can be translated effectively into education research policy and practice.